Study the Antitumor Activity of Copper (II) Complex of 4-Azomalononitrile Antipyrine on Mice Induced With Earlich Ascites Carcinoma Cells (Journal of Environmental Bioremediation and Toxicology, 2014)
Copper (II) complex of 4-azomalononitril antipyrine has been isolated and characterized based on IR spectra, 1H NMR, elemental analyses, molar conductance, electronic spectra and magnetic moment. A diminished amount of antioxidant enzyme coupled with superoxide production inappears to be general characteristic of the tumor cells. This character can be used in cancer treatment. The present study attempted to investigate the effect of copper (II) complex of 4- azomalononitril antipyrine which has SOD like activity on tumor development using Ehrlich ascites carcinoma (EAC) implemented in Swiss albino female mice. The results showed that copper complex with ligand has anti cancer activity in all studied parameters with variable ratios.